Value Stream Mapping at Marks and Spencer Syprus - Loizides, George (2008)
Value Stream Mapping is a lean technique with origins from manufacturing environments and specifically from the factories of the automobile manufacturer Toyota. However, considerable work has been done by researchers to transform the terminology drawn from a manufacturing environment in order to fit other environments. This project is based on this transformation so that Value Stream Mapping can be used in the warehouse, service and office environments of Voici La Mode Ltd. A product family was chosen and by following the flow of products and flow of information through a specific value stream selected, the current state was mapped. The wastes within the value stream were identified with the use of a set of mapping tools and through the future map suggested, the possible ways to eliminate these wastes were provided.